PENGARUH KEPERCAYAAN DAN KEPUASAN PELANGGAN TERHADAP LOYALITAS PELANGGAN - Bahrudin, Muhammad; Zuhro, Siti (Universitas Islam Negeri Sunan Kudus, 2015)
This study aimed to examine and explain the effect of variables of customer satisfaction and trust on customer loyalty in the smartphone Samsung Galaxy.It takes 55 users of smartphones who have Samsung Galaxy in Jombang as the research sample.The sampling technique used non-probability, particularly accidental sampling technique. Data are then analyzed by using multiple linear regression analysis. These results indicate that there is a positive and significant impact of customer satisfaction on customer loyalty and trust on customer loyalty.